El tiempo libre y su incidencia en el rendimiento académico de los estudiantes del colegio expiremental Pio Jaramillo Alvarado sección nocturna, período 2012-2013 - Gómez Feria, Dora Germania (2014)
The present research work entitled “Free time and its incidence on the academic performance on students of “Pío Jaramillo Alvarado High school”, night section, Loja, Academic period 2012-2013”, the general objective is to carry out the Analysis in order to associate the free time and its impact in the academic performance at “Pío Jaramillo Alvarado high school”. To carry out this project there was applied a descriptive study including the deductive, inductive, analytic, synthetic and dialectical methods based on the survey technique, the one that was applied to 112 students sample, as result 75.85% of the surveyed people work in their free time, and their academic performance is 77.67% being very well rated. Conclusions: The different activities that students develop in their time are; working, hanging out with friends, studying and doing assignments A high percentage of students in their free time do assignments, fifty percent of students have from 30 minutes to one hour around of free time a day and the another fifty percent of them have around one to two hours per day.